Operação urbana consorciada: possíveis transformações urbanas e impactos sobre a orla de Belém-PA - SILVA, Felipe Ferreira (2023)
This paper aims to analyze the urban instrument Urban Operation in Belém-PA and its possible application in a waterfront area in the municipality. The analysis starts from a national scale to a local scale, observing the processes involved, the social issues, the project typologies adopted, the ways of enabling and the impacts on the urban environment. In addressing the instrument in Belém-PA, the paper exposes issues related to the occupation of the city's waterfront, quoting projects developed to the area in question, a survey of social data and urban morphology of the area. Finally, a plan for the implantation of an Urban Operation in a section of the riverbank of the municipality is presented, consisting of a guide for the implementation, sectorization, objectives, guidelines and parameters that are convenient to implement the instrument.